Um estranho à minha porta: preparando estudantes de medicina para visitas domiciliares - Ramos-cerqueira, Ana Teresa De Abreu [UNESP]; Torres, Albina Rodrigues [UNESP]; Martins, Sueli Terezinha Ferreira [UNESP]; Lima, Maria Cristina Pereira [UNESP] (Associação Brasileira de Educação Médica, 2009)
This study describes the experience in training first-year students at the Botucatu School of Medicine/UNESP to conduct home visits as part of the course on University-Health Service-Community Interaction. Faculty members from the Departments of Psychology and Psychiatry coordinated the activity, with two groups of 45 students each, by means of the sociodrama technique, which includes warm-up, dramatization, and shared reflections. The main themes brought up by students in the dramatizations were: a) strife and violence; b) poverty and need; c) disappointment and disinterest; d) disempowerment and failure; and e) rejection and distrust. In just a few hours, it was thus possible to experience and elaborate on numerous potentially frightening situations and emotions that are rarely approached during undergraduate medical training. This experience emphasizes the need to prepare undergraduates to make contact with multiple, complex determinants of the health-disease process and act in health care from an interdisciplinary and inter-sector perspective. It is essential for students to have an expanded view of patients within the family and socio-cultural context, drawing on partnership, collaboration, and mutual understanding.

Este trabalho descreve a experiência de preparação de alunos do primeiro ano da Faculdade de Medicina de Botucatu-Unesp para as visitares domiciliares da disciplina Interação Universidade-Serviço-Comunidade. Docentes de Psicologia e Psiquiatria coordenaram a atividade, realizada com dois grupos de 45 alunos por meio da técnica de sociodrama, que inclui as etapas de aquecimento, dramatização e compartilhamento. Os principais temas trazidos pelos alunos nas dramatizações foram: a) briga e violência; b) miséria e carência; c) desapontamento e desinteresse; d) impotência e fracasso; e) rejeição e desconfiança. Assim, muitas situações temidas e emoções raramente abordadas nos cursos médicos puderam ser vivenciadas e elaboradas em poucas horas. Esta experiência reforça a necessidade de preparar o graduando para entrar em contato com os múltiplos e complexos determinantes do processo saúde-doença e para atuar no cuidado à saúde segundo uma perspectiva interdisciplinar e intersetorial. É fundamental que o aluno tenha uma visão ampliada do paciente inserido na sua família e contexto sociocultural, se dispondo a um trabalho de parceria, colaboração e mútuo aprendizado.
A stranger at my door: preparing medical students for home visits
Keywords: Medical education; House Calls; Mental health; Psychodrama; Educação médica; Visita domiciliar; Saúde mental; Psicodrama